Search for protective genetic variants in Alzheimer disease in the U.S. Midwestern Amish: Genetics/genetic factors of Alzheimer's disease. (7th December 2020) - Main, Leighanne R.; Song, Yeunjoo E.; Laux, Renee A.; Miskimen, Kristy; Cuccaro, Michael L.; Ogrocki, Paula; Lerner, Alan J.; Vance, Jeffery M.; Fuzzell, M. Denise; Fuzzell, Sarada L.; Sewell, Jane L.; Lynn, Audrey; et al.
Abstract: Background: Most genetic studies on Alzheimer's disease (AD) have focused on finding risk genes and variants. Taking into account the 30+ loci identified to increase risk of AD, still only around 40‐50% of the estimated heritability of AD is explained. Our goal is to identify genetic variants that delay the onset or protect against the development of AD and to find novel gene interactions or pathways associated with AD. Method: Our study focuses on the Amish communities in Ohio and Indiana due to their homogeneous genetics and environment. Studying genetics in the Amish increases our ability to find rare protective variants for AD that do not exist at a detectable frequency in the general population. Our focus is to identify individuals who are cognitively normal (CN), but at high risk for developing AD (i.e. have an affected sibling). Each of these individuals is retested every two years to assess their cognition status. Results: Using the extensive genealogical data of families in the Amish population, we have generated a large ∼5, 000 person, 13‐generation pedigree. As of January 2020, we have ascertained 652 individuals and are examining over 300, 000 SNPs that were retained after preliminary QC. Out of the recently adjudicated enrollments, 55 percent are cognitively normal, 33 percent are borderline or cognitively impaired, and the remainder have been sampled and are awaiting a consensus diagnosis. The frequency of the APOE‐e2 allele in our enrollments is at 5%, while the APOE ‐e4 allele is at 14%, is lower than the general European population. We are currently using KING and GENESIS software to QC the data since they take into account more relatedness in a population structure, which is needed for working with the Amish. Association and linkage analyses, taking into account the complex pedigree relationships, is ongoing. Conclusion: We are using a founder population to have an increased chance of finding protective genetic variants in AD. We are specifically targeting individuals who are at high risk for developing AD, but seem to be resilient. This is important in discovering novel pathways in which AD functions, which can lead to further functional and pharmaceutical studies.